Laparoscopic greater curvature gastric plication in the treatment of type 2 diabetes - Akzhunus Orekeshova; Oral Ospanov (National Scientific Medical Center, 2016)
The purpose of the study: to evaluate the efficacy of laparoscopic greater curvature gastric plication in the treatment of type 2 diabetes. Methods. The study involved 32 patients suffering from type 2 diabetes and obesity on average 6.87 ± 1.9 years. Results. Participants in a year lost an average weight of 25 kg. Fasting glucose levels dropped significantly within six months after the operation, which correlates with the trend in the weight loss during this period. The average HbA1c for the cohort gradually decreased during the study period from 9.8% to 5.6%. Much of this change occurred during the first six months. Diabetes Remission was achieved in 92% of patients. In patients with remission, hypoglycemic agents were canceled after 4-22 weeks after surgery. Conclusions. Laparoscopic greater curvature gastric plication lowest altering the physiology of the gastrointestinal tract, lowers blood glucose levels in patients suffering from type 2 diabetes and obesity.